A Patient With Severe Lower Face Degloving Injury. Issue 6 (September 2018) - Cavalcante Pita Neto, Ivo; Martins Pereira Lucena Franco, Jéferson; Chaves Moreno, Eduardo; Pita, Pablo; Aurelio Lucchesi Sandrini, Francisco; Gomes de Alencar Gondim, David
Abstract : Abstract: Avulsions of mandible are among the most devastating lesions observed in cranio-maxillofacial traumas. They present an important health problem because of the high risk of morbidity related to deformities that cause functional limitations and esthetic changes. The avulsions commonly result from high-energy effects, which cause complete or partial separation of the mandibular bone of the face. As a result of the intense aggression, the skin and subcutaneous tissues of the bone are usually removed, affecting muscles, fascia, blood vessels, and the surrounding nerves. This article aimed to present a case of partial avulsion of mandible caused by car accident. Here, we emphasize the importance of correctly performing patient stabilization and maintenance of the airways, damage control, and facial reconstruction. Finally, we proceeded with a literature review to discuss standard protocols and controversies in the treatment of these lesions.